Carcinogenesis and Metastasis: Focus on TRPV1-Positive Neurons and Immune Cells - Nuray Erin; Arpad Szallasi (Biomolecules, 2023)
Both sensory neurons and immune cells, albeit at markedly different levels, express the vanilloid (capsaicin) receptor, Transient Receptor Potential, Vanilloid-1 (TRPV1). Activation of TRPV1 channels in sensory afferent nerve fibers induces local effector functions by releasing neuropeptides (most notably, substance P) which, in turn, trigger neurogenic inflammation. There is good evidence that chronic activation or inactivation of this inflammatory pathway can modify tumor growth and metastasis. TRPV1 expression was also demonstrated in a variety of mammalian immune cells, including lymphocytes, dendritic cells, macrophages and neutrophils. Therefore, the effects of TRPV1 agonists and antagonists may vary depending on the prominent cell type(s) activated and/or inhibited. Therefore, a comprehensive understanding of TRPV1 activity on immune cells and nerve endings in distinct locations is necessary to predict the outcome of therapies targeting TRPV1 channels. Here, we review the neuro-immune modulation of cancer growth and metastasis, with focus on the consequences of TRPV1 activation in nerve fibers and immune cells. Lastly, the potential use of TRPV1 modulators in cancer therapy is discussed.